Clinical implications of central blood pressure measured by radial tonometry and automated office blood pressure measured using automatic devices in cardiovascular diseases - Kwon, Ami; Kim, Gee-Hee; Kim, Min-Sik (Frontiers in Cardiovascular Medicine, 2022)
Objective: Central aortic systolic blood pressure (CBP) measured by carotid-femoral pulse wave velocity (PWV) is gold standard method to estimate true arterial pressure. However, the impact of the CBP level measured by radial PWV on cardiovascular (CV) risk assessment is unclear. The aim of this study was to determine the impact on CV outcome assessment and the association between the optimal levels of noninvasively measured CBP and automated office blood pressure (OBP) in clinical practice. Method: A total of 2115 patients underwent noninvasive semiautomated radial artery applanation tonometry (Omron HEM-9000AI) in the Department of Internal Medicine, St. Vincent’s Hospital, from July 2011 to Dec 2015. The patients were followed for at least 5 years and atherosclerotic cardiovascular (ASCVD) outcomes were collected. Results: Among the 2115 patients (mean age 58±14 years, 50.4% men) who were followed up, the median follow-up period was 52 months (range: 1-104 months). The total number of patients with ASCVD events was 163 (7.70%). In multivariate Cox regression analysis, a CBP of more than 125 mmHg and an automated OBP of a more than 131 mmHg were independently associated with significant increase in ASCVD outcomes. After adjusting for confounding factors, the hazard ratio for ASCVD events increased by 12.5%, 11.7%, and 12.7%, for every 10 mmHg increase in automated OBP, CBP and central pulse pressure, respectively. Conclusions: This study demonstrated that the automated OBP measured using the method used in real clinical practice and CBP measured by radial tonometry were associated with an increased risk for adverse ASCVD outcomes.